2012
DOI: 10.5535/arm.2012.36.5.633
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ultrasonography Guided Stellate Ganglion Blockade in the Stroke Patients with Complex Regional Pain Syndrome

Abstract: ObjectiveTo compare the efficacy of ultrasonography guided stellate ganglion block (US-SGB) with that of blind SGB in management of the stroke patients with complex regional pain syndrome (CRPS) type 1.MethodForty-two patients with post-stroke CRPS were randomly assigned to either US-guided SGB (22 patients) or blind SGB group (20 patients). The mean age of US-guided SGB and blind SGB groups was 61.3±5.6 years and 59.1±4.5 years. We performed two blockades at 7-day intervals on the affected side of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 20 publications
3
25
3
2
Order By: Relevance
“…The authors observed a mean pain reduction of 3.2 points on the NRS (relative decrease of 62.7%; initial pain level: NRS = 5.1) after 2 weeks in the group receiving ultrasound‐guided SGB, which is similar to the results regarding the spontaneous pain in the present case series. “Blind” SGB led to a mean pain decrease of NRS 2.6 (relative decrease of 50%; initial pain level: NRS = 5.2) [21].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The authors observed a mean pain reduction of 3.2 points on the NRS (relative decrease of 62.7%; initial pain level: NRS = 5.1) after 2 weeks in the group receiving ultrasound‐guided SGB, which is similar to the results regarding the spontaneous pain in the present case series. “Blind” SGB led to a mean pain decrease of NRS 2.6 (relative decrease of 50%; initial pain level: NRS = 5.2) [21].…”
Section: Discussionmentioning
confidence: 96%
“…Transient side effects occurred in 13.5% of the 156 blocks in this case series, of which hoarseness was the most common. Another study observed no adverse side effects in the group receiving SGB under ultrasound guidance (N = 44 SGBs), whereas two patients from the “blind” group SGB experienced hematoma formation on the injected side (N = 40 SGBs) [21]. Van Eijs et al.…”
Section: Discussionmentioning
confidence: 97%
“…Also, LAs can, on the one hand, by exerting an immediate pharmacological effect favorably influence pain and inflammation (Cassuto et al, 2006;Hollmann and Durieux, 2000;Kirillova et al, 2011;Koppert et al, 1998;Pietruck et al, 2003;Ricker, 1924;Spiess, 1906); and, on the other hand, by being delivered to the stellate ganglion favorably influence pain (Kohjitani et al, 2002;Liu et al, 2013;Masuda and Okamoto, 2005;Noma et al, 2013;Peterson et al, 2009;Pfister and Fischer, 2009;Price et al, 1998;Rosenquist and Vrooman, 2013;Salvaggio et al, 2008;Shanthanna, 2013;Wang et al, 2005;Yoo et al, 2012) and inflammation (Liu et al, 2013;Masuda and Okamoto, 2005;Noma et al, 2013;Pfister and Fischer, 2009;Wang et al, 2005;Yoo et al, 2012). The same beneficial effect on pain and inflammation has also been reported for sympathectomy (Leriche, 1958;Noble et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound (US)‐guided SGB has recently gained popularity. Its growing use in anesthesia, intensive care, and pain medicine is contributed to by the ubiquitous presence of ultrasound probes in clinical areas and low side effect profile when compared to fluoroscopic or blind techniques and the absence of ionizing radiation . Local anesthetics and corticosteroids are typical agents, and additional adjuvants have been proposed to improve analgesia and prolong its effects …”
Section: Introductionmentioning
confidence: 99%